Adaptation to climate change: legal challenges for protected areas - Cliquet, A.; Backes, C.; Harris, Jim A.; Howsam, Peter (Igitur, Utrecht Publishing and Archiving Services, 2009)
Climate change will cause further loss of biodiversity. As negative effects are already taking place, adaptive measures are required to protect biodiversity from the effects of climate change. The EU policy on climate change and biodiversity aims at improving a coherent ecological network in order to have more resilient ecosystems and to provide for connectivity outside core areas. The existing legal framework, the Birds and Habitats Directives, can enable adaptive approaches, by establishing and managing the Natura 2000 network and providing for connectivity measures. However, policy and law so far have mainly been aimed at conserving the status quo of habitats and species within core areas. The question is whether a legal requirement to protect certain species in certain places makes sense when species and even ecosystems are migrating due to climate change. Instead, efforts must be increased to protect ecosystem functions, goods and services from the negative effects of climate change, and to facilitate the ecological restoration of new areas. Even more effort is needed for the implementation of connectivity. If existing legislation proves too weak to face these challenges, a new ‘Ecosystem Framework Directive’ might provide the necessary legal impe